Educating Coaches to Power Dynamics: Managing Multiple Agendas Within the Triangular Relationship. Issue 2 (July 2014) - Louis, Dima; Fatien Diochon, Pauline
<x xml:space="preserve">Abstract</x> Through a study of 20 semistructured interviews using the critical incident method, this article explores the nature of the multiple agendas within the triangular relationship that connects the coach, coachee, and an organization and the challenges associated with their management. The article suggests prerequisites to coaching program applications as well as learning approaches to help coaches embrace the power dynamics associated with their intervention.